Interaction Between the 5-Hydroxytryptamine Transporter-Linked Polymorphic Region (5-HTTLPR) and Negative Life Events in Adolescent Heavy Drinking - Kim, Jueun (J Stud Alcohol Drugs, 2020)
OBJECTIVE: This study investigates whether the reciprocal associations between negative life events and drinking over time differ as a function of 5-HTTLPR (5-hydroxytryptamine [serotonin] transporter-linked polymorphic region) genotype (i.e., candidate gene and environment interaction and correlation) using large and population-based prospective data from adolescents. METHOD: A total of 4,916 White adolescents in the United Kingdom (mean ages = 16, 17, and 18 years old over three assessment points; 47% female) were used. Tri-allelic 5-HTTLPR genotype was assessed; negative life events were assessed at ages 16 and 17; and frequency of heavy drinking was assessed at ages 16, 17, and 18. Path analyses after controlling for covariate interactions and multigroup cross-lagged analyses were conducted. RESULTS: The null findings of candidate gene and environment interaction and correlation were found in the path analyses controlling for covariate interactions, and they were replicated in the multigroup cross-lagged analyses. No moderation by 5-HTTLPR in the association of negative life events at age 16 with heavy drinking at age 17 as well as no association of negative life events at age 17 with heavy drinking at age 18 were found. Also, the 5-HTTLPR genotype did not moderate the association of heavy drinking at age 16 with negative life events at age 17. CONCLUSIONS: Using large prospective data, it appears that there is no evidence for 5-HTTLPR-moderated drinking following experience of negative life events and no support for 5-HTTLPR-moderated selection to negative life events among mid/late adolescents. This finding may inform developmental patterns in gene and environment interaction effects by showing that the effects are less pronounced in mid/late adolescence than in early adolescence.